Leakage of Octyl(Phenyl)--Di-Isobutylcarbamoylmethylphosphine Oxide from a Macroporous Silica-Based Chelating Polymeric Adsorption Material and its Recovery by Some Selected Porous Adsorbents - Anyun Zhang; Yuezhou Wei; Harutaka Hoshi; Mikio Kumagai; Yoshikazu Koma (Adsorption Science & Technology, 2005)
The leakage behaviour of a neutral chelating agent, i.e. octyl(phenyl)- N,N -di-isobutylcarbamoylmethylphosphine oxide (CMPO), from its macroporous silica-based (CMPO/SiO 2 -P) extraction resin (a novel polymeric adsorption material developed in the MAREC process) and the recovery of CMPO by some selected polymer- and silica-based porous adsorbents were investigated by column operation in 0.01 M HNO 3 at 25°C or 50°C. The concentration of CMPO in the effluent leaking from CMPO/SiO 2 -P was determined as ca. 48 ppm at 25°C and ca. 37 ppm at 50°C. The corresponding elution volumes and the amounts of CMPO leaking were 8700.9 BV/g and 239.3 mg/g at 25°C and 11 842.9 BV/g and 359.4 mg/g at 50°C, respectively. The adsorption experiment showed that a polymer-based porous material, SEPABEADS® SP-825, was capable of recovering CMPO effectively from 0.01 M HNO 3 . Its adsorption ability towards CMPO was considerably greater than those of macroporous silica-based SiO 2 -P particles, polymer-based Amberlite™ XAD-7 and activated carbon. The bed volume and the amount of CMPO adsorbed by SEPABEADS® SP-825 at the breakthrough point at 25°C were 13 549.2 BV/g and 498.7 mg/g, respectively, thereby demonstrating that SEPABEADS® SP-825 was promising for the recovery of CMPO from Am(III)- and Cm(III)-containing solutions in the MAREC process.